2009
DOI: 10.12671/jkfs.2009.22.4.232
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Hemiarthroplasty Using the Greater Trochanter Reattachment Device (GTRD) for Comminuted Intertrochanteric Femur Fracture in Elderly Patients

Abstract: Purpose: To evaluate the clinical and radiological outcome of the greater trochanter reattachment device (GTRD) as firm fixation method for displaced greater trochanter fragment in bipolar hemiarthroplasty for comminuted intertrochanteric femur fracture in elderly patients. Materials and Methods:From January 2006 to January 2008, 32 patients above 70 years old treated with bipolar hemiarthroplasty using the GTRD as fixation method for comminuted intertrochanteric femur fracture with greater trochanter bone fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In cases where comminuted fractures of the greater trochanter are accompanied by reverse oblique inter trochanteric femoral fracture, anatomical reduction and rigid fixation of bone fragments are significant due to consequences including hip pain and changes in the lever arm covering the center of the hip throughout to the abductor muscle's point of action, potentially resulting in dislocation of an artificial joint due to weakened abductor muscles 25) . Various surgical techniques are being utilized for treating unstable intertrochanteric femoral fractures via BHA 26 27 28) . In the present study, we utilized the tension band wiring technique which fixes the lesser trochanter with a circular steel wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where comminuted fractures of the greater trochanter are accompanied by reverse oblique inter trochanteric femoral fracture, anatomical reduction and rigid fixation of bone fragments are significant due to consequences including hip pain and changes in the lever arm covering the center of the hip throughout to the abductor muscle's point of action, potentially resulting in dislocation of an artificial joint due to weakened abductor muscles 25) . Various surgical techniques are being utilized for treating unstable intertrochanteric femoral fractures via BHA 26 27 28) . In the present study, we utilized the tension band wiring technique which fixes the lesser trochanter with a circular steel wire.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, another steel wire was penetrated through the upper greater trochanter and the lesser trochanter in an "8" shape 28) . The advantages of the technique included its simplicity, its lack of effect on surgical costs, and the lack better bone union, bursitis, bone resorption, and damage to the metal plates employed for rigid fixation 26) . In particular, it reduces operation time, which may be crucial for faster recovery times in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In bipolar hemiarthroplastys performed for the management of comminuted unstable intertrochanteric fractures, since non-union and displacement of the greater trochanteric fragment attached with the abductor muscles may cause pain, limping and hip dislocation, several studies have suggested using different fixation methods to manage the greater trochanteric fragment89101112). Koyama et al15) proposed a fixation technique using a multifilament cable grip in revision hip arthroplasty after a greater trochanteric osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Hemiarthroplasty is one surgical treatment option for the management of unstable intertrochanteric fractures in older adults by allowing early ambulation after surgery, preventing several complications caused by prolonged bed rest, and having a positive effect on gait restoration567). Since fixation failure of the greater trochanteric fragment, the attachment site for the abductor muscles, may cause pain, limping and dislocation of the hip, a variety of fixation methods have been introduced to obtain solid fixation of bone fragments89101112). However, studies on the classification of greater trochanter (GT) fractures and fixation methods according to the type of GT fracture have been rarely performed.…”
Section: Introductionmentioning
confidence: 99%